Trypanosoma cruzi Genomic Variability: Array Comparative Genomic Hybridization Analysis of Clone and Parental Strain - Cortez, Danielle Rodrigues; Lima, Fabio Mitsuo; Reis-Cunha, João Luís; Bartholomeu, Daniella Castanheira; Villacis, Rolando Andre Rios; Rogatto, Silvia Regina; Costa-Martins, André Guilherme; Marchiano, Fernanda Sycko; do Carmo, Rafaela Andrade; da Silveira, Jose Franco; Marini, Marjorie Mendes (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosoma cruzi, the etiological agent of Chagas disease, exhibits extensive inter- and intrastrain genetic diversity. As we have previously described, there are some genetic differences between the parental G strain and its clone D11, which was isolated by the limiting dilution method and infection of cultured mammalian cells. Electrophoretic karyotyping and Southern blot hybridization of chromosomal bands with specific markers revealed chromosome length polymorphisms of small size with additional chromosomal bands in clone D11 and the maintenance of large syntenic groups. Both G strain and clone D11 belong to the T. cruzi lineage TcI. Here, we designed intraspecific array-based comparative genomic hybridization (aCGH) to identify chromosomal regions harboring copy-number variations between clone D11 and the G strain. DNA losses were more extensive than DNA gains in clone D11. Most alterations were flanked by repeated sequences from multigene families that could be involved in the duplication and deletion events. Several rearrangements were detected by chromoblot hybridization and confirmed by aCGH. We have integrated the information of genomic sequence data obtained by aCGH to the electrophoretic karyotype, allowing the reconstruction of possible recombination events that could have generated the karyotype of clone D11. These rearrangements may be explained by unequal crossing over between sister or homologous chromatids mediated by flanking repeated sequences and unequal homologous recombination via break-induced replication. The genomic changes detected by aCGH suggest the presence of a dynamic genome that responds to environmental stress by varying the number of gene copies and generating segmental aneuploidy.